Humanities and Big Data in Ibero-America: Theory, methodology and practical applications - Gallego Cuiñas, Ana; Torres-Salinas, Daniel (Humanidades Digitales y Big Data en Iberoamérica / Digital Humanities and Big Data in Ibero-America, 2024)
This volume presents the first comprehensive study on the relationship between the Human Sciences and Big Data, with special emphasis on the Ibero-American space. The volume is divided into three parts (theoretical, methodological and practical) with an interdisciplinary vision that integrates thought, culture, language, literature, theoretical criticism, society or the use of new bibliometric techniques.